Vpliv spanja na zdravje in telesno pripravljenost športnikov - Kožar, Nika (Šport (Ljubljana), 2023)
Sleep has a significant effect on athlete’s health and performance. Nevertheless, sleep in sports often remains neglected and poorly researched. Athletes often do not get enough nocturnal sleep and can have poor sleep quality. In addition to training and competitions (intensity, load, schedule, travel), athlete’s sleep is also affected by: electronic devices, environmental factors (altitude, heat/cold) and by menstrual cycle in female athletes. In addition to general sleep deprivation, other sleep disorders present among athletes include obstructive sleep apnea, insomnia, and circadian rhythm disorders. There are several practical and affordable ways to monitor and measure athlete’s sleep. The latter include questionnaires, sleep diary and the use of applications and devices. With good sleep hygiene and by education athletes about sleep, athlete’s sleep can be improved. With the aim of raising awareness about the effect of sleep on athlete’s health and performance, in this paper, we researched sleep among athletes in greater detail and present practical tools for measuring, monitoring and improving athlete’s sleep.
Keywords: kronotip; motnje spanja; spanje; šport; športniki; telesna pripravljenost